Political psychology a social psychological approach - Hewer, Chris 1957-; Lyons, Evanthia (BPS textbooks in psychology, 2018)
The text puts the emphasis on alternative approaches to psychological enquiry that challenge our traditional assumptions about the world. With contributions from an international panel of experts, the text contains a meaningful exchange of ideas that draw on the disciplines of social psychology, sociology, history, media studies and philosophy. This important text offers a broader understanding of the different intellectual positions that academics may take towards political psychology. Comprehensive in scope Political Psychology provides a historical context to the subject and offers a critical history of common research methods. The contributors offer insight on political thought in psychology, the politics of psychological language, narrating as political action, political decision-making and much more. This text: Includes a review of some political ideas associated with the work of Karl Marx, Erich Fromm, R.D. Laing, Michel Foucault and others -- Presents information on prejudice, stereotypes and discrimination in the context of mass migration -- Reviews a wide range of relevant topics such as identity, social exclusion and foreign policy and more -- Contains questions for group debate and discussion at the end of each chapter.